The self-perceived health-care needs of patients with bipolar disorder in Nigeria. (2018)
Few studies have examined the health care needs of patients with bipolar disorder. The aim of this study was to comprehensively assess the clinical and social needs of patients with bipolar disorder in Nigeria and to study the demographic and clinical correlates of such needs. This was a cross-sectional study. Consecutive and consenting out patients with bipolar disorder (n = 100), were assessed with the Camberwell Assessment of Needs Short Appraisal Schedule, the Interpersonal Support Evaluation List-Shortened Version (ISEL-12), the World Health Organization Quality of life-BREF and the Young Mania Rating Scale (YMRS). The most frequently rated areas of total needs as well as unmet needs were in the domain of sexual expression, intimate relationships and the need for company. The mean number of total needs per participant was 10.70 while the median number of unmet needs was 1.50. The total number of unmet needs was significantly higher for unremitted participants compared to remit ted participants. The total number of unmet needs was positively correlated with the severity of manic symptoms (YMRS score) and negatively correlated with the level of social relationships (social domain of WHOQOL), functioning (Global Assessment of Functioning (GAF) score) and social support (Tangible Support subscale of the ISEL). The GAF score and YMRS score significantly predicted unmet needs. The study underscores the importance of assessing the needs of patients with bipolar disorder in Nigeria.